Select readings in economics - Harris, C. Lowell (Columbia)
The book is for the student of elementary economics and for his teacher It is a supplement to standard textual material. Instructors know and students sense that textbooks do not contain all that a basic course should provide illustrative material, a variety of points-of-view, application of tools of analysis. contact with classics, different ways of stating an important point. A wealth of material with which to enrich the course exists, but searching out the best of it is not easy. Making it readily accessible is even more difficult, for seldom is it available in edited form; nor can libraries often furnish sufficient copies. Thus, a real need exists. This volume is designed to help meet it.
Keywords: Economics